Implementasi Pembelajaran Tematik pada Kurikulum 2013 di Madrasah Ibtidaiyah Negeri Sumbersari Kabupaten Jember - ., Mukniah (IJIT: Indonesian Journal of Islamic Teaching, 2018)
Madrasah Ibtidaiyah Negeri Sumbersari is an institution appointed by the Ministry of Religion of Indonesia to implement the Curriculum 2013 both on thematic and religious learning in accordance with the Decision of Director General of Islamic Education No. 481 of 2015 on Stipulation of Madrasah Assistance 2013 Curriculum Implementation. How to implement thematic learning in 2013 curriculum in Madrasah Ibtidaiyah Negeri Sumbersari Jember Regency. Some of the elements used as the focus of this research are how the implementation of thematic learning in the curriculum 2013 in setting the lesson theme in Madrasah Ibtidaiyah Negeri Sumbersari Jember regency, how the implementation of thematic learning in the curriculum 2013 in the principles of determining the theme, how the implementation of thematic learning in the 2013 curriculum in setting the theme network, and how the implementation of thematic learning in the 2013 curriculum in Madrasah Ibtidaiyah Negeri Sumbersari Jember District. Through the qualitative research, the results of research show that: First, the implementation of thematic lesson in the curriculum 2013 at Madrasah Ibtidaiyah Negeri Sumbersari, in the process of determining the theme, the teacher and students is not the one who create the theme, instead the theme has been determined by the Ministry of Education and Culture of Indonesia with the issuance of Permendikbud No 57 of 2014. Second, Implementation of thematic lesson in the 2013 curriculum at Madrasah Ibtidaiyah Negeri Sumbersari in the principle of determining the theme based on the principles that pay attention to students' environment, train students to think, and according to the development, interest, and the students need. Thirdly, the implementation of thematic learning in the 2013 curriculum at Madrasah Ibtidaiyah Negeri Sumbersari in determining the theme network is done by the theme network interaction in the implementation of thematic learning and the theme network that already exist in the teacher handbook. Fourth, the implementation of thematic learning in the 2013 curriculum at Madrasah Ibtidaiyah Negeri Sumbersari in the implementation of learning activities includes: preliminary activities, core activities, and closing activities.